THE CONCEPT OF IMMUNOMODULATION IN AYURVEDA W.S.R. TO ITS SIGNIFICANCE IN PREVENTING EMERGING INFECTIONS LIKE COVID 2019 (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is one of the most renowned traditional systems of medicine that has survived and flourished from ages till date. The two basic aims of Ayurvedic science is to maintain the health of healthy person and curing the ill health of the diseased. Here is a comprehensive review of the Ayurvedic classical texts, to understand the Ayurvedic perspectives of immunomodulation w.s.r. to its significance in preventing emerging infections like COVID 2019 pandemic. Background: The review is prepared based on the Ayurvedic perspectives and practices of immunity described in various classical Ayurvedic text books like Brhitrayis, Laghutrayis, their commentaries and published research articles. Review Results: Ayurveda enlists various enhancers of immunity, which include Dinacharya (daily regimen), Ritucharya (seasonal regimen), proper diet, exercise, specific foods like milk, Rasayanas like Guduchi (Tinospora cordifolia), meditation, Yoga-pranayama, Achara Rasayana (good conduct of behaviour). The concept of Vyaadhiksamatva is not merely immunity against a specific infectious agent or disease like the concept of modern medicine. Rather, it denotes resistance against the loss of integrity, proportion and inter-relationship amongst the individual’s Doshas (biohumours) and Dhatus (tissues), which can be increased by various methods mentioned in Ayurveda. Conclusion: New infections are emerging which are not manageable by conventional medicine like the COVID 2019 pandemic. Soit is high time to educate people about the valuable teachings on leading a healthy and subsequently a happier life with the help of the immunomodulatory techniques described in Ayurveda.